Giuseppe Bianchini (1888-1973): the father of Italian forensic mycology - Davide Orsini; Simone Di Piazza; Mirca Zotti; Mariano Martini (Italian Journal of Mycology, 2022)
Giuseppe Bianchini trained within the Sienese School of Forensic Medicine and immediately distinguished himself for his innovative approach to the discipline, making very important use of biochemistry, haematology, histopathology, and physiology. During his long career as a scholar and professor of forensic medicine, an important part of his research was the study of the ‘biology of the corpse’, for which he was inspired by the presence of fungi on cadaveric material. Indeed, Bianchini considered the study of fungi, which was completely ignored at the time, to be of particular interest both in terms of the chemistry of the corpse and in determining the chronology of death. He was the first in Italy to attempt to identify and describe a mycological biota in the different states of decomposition of the corpse.